(untitled) (Swiss Medical Weekly, 2018)
BACKGROUND AND AIM Wilson’s disease is an inherited disorder of hepatic copper metabolism, leading to the accumulation of copper in the liver as well as the brain, cornea and other organs. Here, we describe the adult cases of hepatic Wilson’s disease diagnosed at the Division of Gastroenterology and Hepatology of the University Hospital Lausanne, Switzerland between September 2004 and August 2016. METHODS Clinical manifestations, results of diagnostic tests, management and outcomes of adult patients with hepatic Wilson’s disease were assessed based on standardised medical records. In addition, liver histology was reviewed and the lesional patterns were recorded. RESULTS Ten new adult cases of hepatic Wilson’s disease were diagnosed in our centre between September 2004 and August 2016. Male to female ratio was 1:1 and median age at diagnosis was 26 (range 18–56) years. Four patients presented with acute liver failure, four with persistently elevated liver function tests, and two with decompensated cirrhosis; none had neurological manifestations. Only one patient had a Kayser-Fleischer corneal ring. Median ceruloplasmin level at diagnosis was 0.13 (range <0.03–0.30) g/l, median 24-hour urinary copper excretion was 2.8 (range 0.3–77.3) μmol, and median hepatic copper concentration was 789 (range 284–1677) μg/g. At least one mutation in the ATP7B gene was identified in eight patients. Allelic frequency of the common H1069Q mutation was 19%. Leipzig score was ≥5 in all patients. Three patients presenting with acute liver failure and the two with decompensated cirrhosis underwent successful liver transplantation. One patient with acute liver failure recovered under chelation therapy, as predicted by a Dhawan score <11. D-penicillamine was used as first-line chelator treatment, with a subsequent switch to trientine due to adverse effects in three out of six patients. CONCLUSIONS The clinical presentation of hepatic Wilson’s disease is highly variable. Three out of 10 patients were diagnosed at an age >35 years. A high index of suspicion in clinically compatible situations is key.